2019
DOI: 10.1088/1748-9326/ab309e
|View full text |Cite
|
Sign up to set email alerts
|

Local land-use decision-making in a global context

Abstract: Land-use change has transformed the majority of the terrestrial biosphere, impacting biodiversity, climate change, food production and provision of multiple ecosystem services. To improve our understanding of land-use change processes, the motivations and characteristics of land-use decisionmakers need to be addressed more explicitly. Here, we systematically review the peer-reviewed literature between 1950 and 2018 that documents decision-making underlying land-use change processes. We found 315 publications r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 70 publications
0
43
0
Order By: Relevance
“…However, despite growing awareness of these concepts, their practical application is still limited, and the core problem has not been fully addressed. Economic objectives continue to be of overriding importance for land-use decision-making, regardless of the type of decision-maker involved [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite growing awareness of these concepts, their practical application is still limited, and the core problem has not been fully addressed. Economic objectives continue to be of overriding importance for land-use decision-making, regardless of the type of decision-maker involved [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research that highlights observed similarities among social-ecological contexts such as land system archetypes (Václavík et al, 2013) or decision-making types (Malek et al, 2019), can also aid identification of shared major processes (Rocha et al, 2019) or drivers of change (Harrison et al, 2018). A separate benefit of adopting a 'high-level' process approach is that the resulting models are likely to be widely understandable because the processes accord with those experienced by actors and stakeholders in any given system.…”
Section: Ways Out Of 'The Mess'mentioning
confidence: 99%
“…They are intended to do so by focusing on general processes from which changes emerge (Figure 1), rather than providing a description of variation at a certain time, or specific effects or situations that lead to breakdowns. Research that highlights observed similarities among social–ecological contexts such as land system archetypes (Václavík et al., 2013) or decision‐making types (Malek et al., 2019), can also aid identification of shared major processes (Rocha et al., 2019) or drivers of change (Harrison et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To fill this gap, Malek et al [37] conducted a metaanalysis of case-studies to identify where, and under what conditions, certain modes of land-use decision making are found. The occurrence of archetypes of decision making, ranging from satisficing behavior to utility maximization, was related to contextual conditions, leading to a predictive model that indicates what mode of land use decision making can be expected in a particular context (Figure 1).…”
Section: Embrace Complexity and Diversity Of Human Agencymentioning
confidence: 99%
“…Environmental SustainabilityResults of a meta-analysis of case studies reporting decision-making modes worldwide. Left: Radar charts showing average scores on abilities (financial, land size, land tenure, connectedness, power), objectives (survival, economic, environmental, lifestyle, social prestige) and attitudes (change, legislation, environmental values) for the different decision-modes; Right: Maps depicting likelihood of finding a specific decision mode based on extrapolation with socio-economic and biophysical context variables[37].…”
mentioning
confidence: 99%